Time Wealth as a Determinant of Public Transport Behavior: Empirical Evidence from Japan - Chun-Chen Chou; Kenji Doi; Kento Yoh; Masanobu Kii (Urban Science)
In low-demand areas, optimizing public transport operations requires strategies that go beyond infrastructure improvements. Among the various influencing factors, time wealth—the perceived freedom and flexibility in managing one’s time—emerges as a critical component in encouraging public transport use. Temporal factors like time cost and scheduling inconvenience often hinder usage, making time-related perceptions essential for effective and inclusive transport strategies. This study investigates time wealth as a component of perceived behavioral control in shaping public transport intention. Using empirical surveys in Japan, factor analysis and structural equation modeling identified three dimensions of time wealth and assessed their influence on behavioral intention. Results show that greater time wealth reduces the perceived difficulty of using public transport, thereby enhancing user intention. Positive attitudes and awareness support effective public transport interventions. While improving accessibility and convenience is important, addressing fare affordability is equally vital. A balanced approach that enhances both the experiential and financial aspects of public transport is crucial for maximizing its utilization. These findings highlight the need for integrated strategies that enhance both temporal and financial aspects to boost public transport use.